Parishin E from ginger-processed Gastrodia elata Bl. alleviates rheumatoid arthritis by regulating histone 3 lactylation at H3K18la and H3K27la sites - Liu, Xinyue; Pan, Yijing; Deng, Chenxi; Zhu, Meiliang; Guo, Dongmei; Wu, Jiaqin; Feng, Fan; Pan, Lianhong; Wang, Chunli; Xu, Kang (Frontiers in Pharmacology, 2025)
BackgroundThis study investigated the natural small molecule drug Parishin E (PE) derived from the orchid plant Gastrodia elata Bl. (GEB). We evaluated the therapeutic effects of ginger-processed Gastrodia elata Bl. (G-GEB) on rheumatoid arthritis (RA) and focused on paracine E to elucidate its potential regulatory mechanisms.MethodsAn Sprague-Dawley rat model of rheumatoid arthritis was constructed to evaluate the pharmacological effects of G-GEB. Plant non-targeted metabolomics, serum non-targeted metabolomics, and RAW264.7 inflammation models elucidate Parishin E as the core anti-inflammatory component of G-GEB. Subsequently, transcriptomic and metabolomic analyses were performed to elucidate the molecular signaling mechanism of Parishin E in the treatment of RA.ResultsG-GEB significantly improves RA, with 363 active compounds identified by untargeted metabolomics. PE, its main active component, affects cell glycolysis by downregulating HK2 and LDHA to inhibit macrophage polarization. PE also shows anti-inflammatory properties by suppressing H3 lactylation at H3K18la and H3K27la.ConclusionPE in G-GEB exerts an RA ameliostatic effect by inhibiting macrophage polarization by regulating cellular glycolysis and by inhibiting the emulsylation modification of histone H3 sites, specifically H3K18la and H3K27la. Therefore, PE is a promising drug candidate for the development of RA treatments.